Bezrobocie w Polsce i UE – najważniejszy element polityki zatrudnienia - Ślusarczyk, Bogusław (MITEL, 2006)
Najważniejszym wyzwaniem dla polityki zatrudnienia Unii Europejskiej i Polski jest regulacja rynku pracy, a przede wszystkim ograniczenie skali bezrobocia. Realizacja zadania polega na wykorzystaniu funduszy strukturalnych m.in. Europejskiego Funduszu Społecznego. Polityka w Polsce powinna skutkować ograniczeniem bezrobocia do 2010 roku w skali ok. 2-3%.

The most important challenge for European Union and Poland employment policy is regulation of labour market and, above all, limiting the unemployment scale. Fulfilment of the task consists in using structural funds, among others European Social Fund. The policy in Poland should result in limiting unemployment till 2010 year in a scale of about 2–3%.
Unemployment in Poland and EU – the Most Important Element of Employment Policy